2009
DOI: 10.1093/nar/gkp671
|View full text |Cite
|
Sign up to set email alerts
|

Human Pif1 helicase unwinds synthetic DNA structures resembling stalled DNA replication forks

Abstract: Pif-1 proteins are 5′→3′ superfamily 1 (SF1) helicases that in yeast have roles in the maintenance of mitochondrial and nuclear genome stability. The functions and activities of the human enzyme (hPif1) are unclear, but here we describe its DNA binding and DNA remodeling activities. We demonstrate that hPif1 specifically recognizes and unwinds DNA structures resembling putative stalled replication forks. Notably, the enzyme requires both arms of the replication fork-like structure to initiate efficient unwindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 40 publications
(54 reference statements)
4
79
0
Order By: Relevance
“…Thus, it was proposed that PIF1 function is redundant in mammalian cells. Nevertheless, in vitro analysis of purified full-length PIF1 suggested that it bound and unwound DNA structures that might form during DNA replication stress, including structures resembling stalled replication forks (14) or G-quadruplexes (28). The effects of PIF1 depletion on S-phase transition, checkpoint activation, and apoptosis in tumor cells are consistent with these in vitro results; however, nontumor cell lines did not show similar responses.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Thus, it was proposed that PIF1 function is redundant in mammalian cells. Nevertheless, in vitro analysis of purified full-length PIF1 suggested that it bound and unwound DNA structures that might form during DNA replication stress, including structures resembling stalled replication forks (14) or G-quadruplexes (28). The effects of PIF1 depletion on S-phase transition, checkpoint activation, and apoptosis in tumor cells are consistent with these in vitro results; however, nontumor cell lines did not show similar responses.…”
Section: Discussionsupporting
confidence: 61%
“…In vitro assays of PIF1 binding and unwinding on artificial substrates resembling replication forks (14) suggested that PIF1 could play a role in the generation of ssDNA that triggers activation of CHK1. Consistent with this argument, CHK1 activation, which is dependent upon ssDNA formation (23), was lower in PIF1-depleted cells exposed to thymidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that Mcm2-7 may be unable to unwind the final portion of DNA between the converging replication forks, leaving only Pfh1 to perform this function. In this regard, it is interesting to note that human Pif1 can unwind synthetic replication forks in vitro in a way that could promote progression of the leading strand polymerase in vivo (George et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…ScRrm3 also promotes fork progression at other sites where ScPif1 is not known to act, such as at tRNA genes, inactive origins, and the silent mating type loci, while ScPif1 is important for replication through G-rich motifs that can form G-quadruplex structures in vitro (Ivessa et al 2003;Paeschke et al 2011). Human Pif1 (hPif1) also unwinds G-quadruplex structures in vitro, as well as DNA structures that resemble stalled replication forks (George et al 2009;Sanders 2010). Although S. cerevisiae Pif1 family helicases have important roles in DNA replication, pif1D rrm3D cells are viable (Ivessa et al 2000).…”
mentioning
confidence: 99%